Towards A More Environmentally Friendly Nigeria: The Eco-Theatre for Children Initiative - Okoro, Lilian; Otonko, Juliana Sewuese (Universitas PGRI Madiun, 2024)
In Nigeria, despite numerous efforts to promote environmental safety, progress has been limited. Many young people, particularly children, need greater awareness of climate change's consequences, such as food scarcity. This paper examines the potential of eco-theatre as an effective tool for children's theatre to enhance environmental awareness among youth. By equipping children with knowledge about the importance of fostering a more eco-friendly Nigeria, children’s theatre plays a crucial role. Utilizing participatory action research and drama, this study addresses harmful environmental practices such as bush burning, deforestation, and bush meat hunting by highlighting their negative impacts and empowering children to advocate for environmental preservation. The paper showcases a children’s theatre production,